2013
DOI: 10.4137/cmamd.s11768
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes and Predictors of Clinical Success with the KineSpring Knee Implant System

Abstract: The purpose of this study was to (1) evaluate joint pain and function in knee osteoarthritis (OA) patients treated with a joint-sparing, extracapsular implant and (2) identify patient characteristics that influenced clinical outcomes. This study included 99 patients with symptomatic medial knee OA refractory to conservative care who were treated with the KineSpring Knee Implant System and followed for a mean of 17 months (range, 1.5 to 48 months). All devices were successfully implanted and activated with no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…A recent study of 99 patients with 17 months mean follow-up reported excellent safety and effectiveness outcomes 78. All devices were successfully implanted and activated with no intraoperative complications.…”
Section: Emerging Technologies For the Young Post-traumatic Knee Oa Pmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study of 99 patients with 17 months mean follow-up reported excellent safety and effectiveness outcomes 78. All devices were successfully implanted and activated with no intraoperative complications.…”
Section: Emerging Technologies For the Young Post-traumatic Knee Oa Pmentioning
confidence: 89%
“…The initial clinical experience with this implant is promising 78. A recent study of 99 patients with 17 months mean follow-up reported excellent safety and effectiveness outcomes 78.…”
Section: Emerging Technologies For the Young Post-traumatic Knee Oa Pmentioning
confidence: 99%
“…2 Additional studies are underway to further characterize the safety and efficacy of this novel implant for treatment of medial knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-capsular (non-articular) medial compartment knee load absorber implants fixed to the medial distal femoral cortex and the medial proximal tibial cortex to achieve offloading of the medial compartment are under evaluation 31 , 32 . A recent series of patients with Kellgren-Lawrence grade I or II knee OA treated with this joint unloading implant and followed for at least 1 year reported a 70% decrease in WOMAC Pain, a 68% decrease in WOMAC Function, and a 59% decrease in WOMAC Stiffness scores 33 , 34 . The premise of these implants is that the device is surgically implanted via a minimally invasive incision, the joint remains fully intact, the procedure is reversible, and the medial knee compartment is unloaded sufficiently to reduce pain and improve joint function.…”
Section: Early Knee Osteoarthritis Managementmentioning
confidence: 99%